Why Did God Want to Kill Moses? The Image of the Dangerous God in Exodus 4:24-26 - BALOGH, Csaba (Studia Universitatis Babeș-Bolyai Sacra Scripta, 2026)
The strange pericope of Ex 4:24–26 is discussed in numerous studies, mainly from the perspective of religious history or rhetorical criticism. Building on the results of previous research, this study confirms earlier suggestions that this passage cannot be connected well with its direct context, specifically with the larger call narrative of Ex 3:1–4:18, or with the smaller preceding unit in vv. 20–23. The observations regarding rhetorical and logical problems around Ex 4:19.24–27 are corroborated by independent text-historical arguments, derived mainly from the Old Greek version. It is also unlikely though that Ex 4:24–26 would be an entirely independent segment in the Moses-tradition. The narrative in its earliest form (reconstructed here as consisting of vv. 19.24–26) was the original follow-up of Ex 2, specifically 2:23a. It is this particular context which unveils YHWH’s stance towards Moses. The intention of this alternative Moses-story differs from the better-known Ex 3:1–4:18.